Opportunities and Challenges that the Implementation of Group Work Activities Bring to Promote Fifth Graders’ Interaction in the English Class (2023)
ABSTRACT: This action-research aimed at identifying and reflecting about the opportunities and challenges that the implementation of group work activities can bring to promote interaction in a group of fifth graders. It was conducted in a public school in El Carmen de Viboral, Antioquia with 34 fifth graders. Action strategies included how applying group work activities can promote interaction among students. Data gathering instruments included teacher’s journal, checklist, students’ reflections, and focus group. Findings referred to participants, including me; as follows: opportunity to apply group work activities helped students make informed and group decisions about the development of the activity and their responsibilities, and allowing students to work in groups gave them the means to share their knowledge and opinions, ask for corrections and give feedback, giving students the freedom to change groups along the process, caused disorganization within the groups limiting interaction with peers.